2021
DOI: 10.2147/ndt.s310010
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Sensitivity Mediates the Effects of Childhood Maltreatment on the Evaluation of Life Events and Anxiety States in Adult Community Volunteers

Abstract: Background Childhood maltreatment has long-lasting psychological effects, which often manifest in adulthood. Previous studies have suggested that the effects of childhood maltreatment are not only direct but also indirect, being mediated by other factors. In this study, we hypothesized that the effects of childhood maltreatment on state anxiety in adulthood are mediated by interpersonal sensitivity and the evaluation of life events, and investigated this possibility by covariance structure analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 35 publications
4
20
1
Order By: Relevance
“…Harb et al 22 reported that a group of patients with social anxiety disorder had higher IPS than controls. The association between IPS and anxiety disorders has also been reported by Wilhelm et al 23 We previously reported that IPS had a direct positive effect on state anxiety 20 . Furthermore, we found that the impact of IPS on state anxiety was mediated by evaluating life events negatively 20 …”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Harb et al 22 reported that a group of patients with social anxiety disorder had higher IPS than controls. The association between IPS and anxiety disorders has also been reported by Wilhelm et al 23 We previously reported that IPS had a direct positive effect on state anxiety 20 . Furthermore, we found that the impact of IPS on state anxiety was mediated by evaluating life events negatively 20 …”
Section: Introductionsupporting
confidence: 84%
“…Regarding childhood maltreatment, which occurs in similar contexts as negative parenting styles, our previous studies by Otsuka et al 51 and Nakazawa et al 20 reported that the impacts of childhood maltreatment enhance IPS. These studies also enabled us to predict the results of this study to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations